Tortas de oleaginosas na terminação de ovinos em pastos de capim-tanzânia - Silva, Leane Veras da (2020)
The objective was to evaluate the replacement of soybean meal (control) with oilseed cakes: cottonseed, babassu, and castor bean cakes, in supplements for sheep on Tanzania grass. Two experimental trials were carried out using 24 Morada Nova crossbred sheep with 15.85±1.3 kg average initial weight in a completely randomized design with six replications, using Dunnett’s test (P<0.05) comparing the averages of each supplement in relation to the control. The first test evaluated dry matter intake (DMI, g day-1), dry matter intake (DMI, %BW), crude protein intake (CPI), neutral detergent fiber intake (NDFI); and the dry matter digestibility (DDM), crude protein digestibility (CPD), neutral detergent fiber digestibility (NDFD), and ether extract digestibility (EED). Evaluations were also carried out for average daily gain (ADG), total weight gain (TWG), and number of days required to gain 12 kg (D12). DMI for animals fed the supplement containing babassu cake was lower, following the same behavior for CPI and NDFI. There was a substitution effect for DMI in animals supplemented with babassu cake in relation to the control. On the other hand, DDM, CPD, and NDFD were lower for animals fed the supplement based on soybean meal, due to the inclusion of rice husk, which contains indigestible CP and NDF. ADG and TWG were higher for lambs supplemented with soybean meal, resulting in a higher final weight, compared to the treatment with cottonseed cake and babassu cake. The D12 in animals supplemented with castor bean cake was similar to the control and allowed to finish a greater number of batches per year. When the first group of animals reached an average body weight of 29 kg and were sent for slaughter, the second trial determined the biometric measurements after slaughter, the hot carcass weight and yield, cold carcass weight and yield, and morphometric measurements of the carcass. Carcasses were cut lengthwise, and the left half-carcass was divided into commercial cuts: neck, shoulder, serrote, ribs, loin, and shank. Meat quality analyses considered the water holding capacity, cooking losses, shear force, total lipids, cholesterol, fatty acid profile, and atherogenicity index. There was a higher cold carcass yield in animals fed the supplement containing castor bean cake. Cooking losses were greater in meat from animals supplemented with babassu cake and shear force was greater for meat from animals fed cottonseed cake. The supplement containing castor bean cake resulted in a higher content of conjugated linoleic acid (C18_2c9t11) in sheep meat. Castor bean cake is the best alternative to replace soybean meal by up to 45.17% in the formulation of dietary supplements for sheep.